Tribological and machining characteristics of an electrostatic minimum quantity lubrication (EMQL) technology using graphene nano-lubricants as cutting fluids. (August 2018) - Lv, Tao; Huang, Shuiquan; Liu, Enting; Ma, Yaliang; Xu, Xuefeng
Abstract: To improve machining performance and lower oil mist concentration in machining workshops, a near-dry machining technique called "electrostatic minimum quantity lubrication (EMQL)" was proposed, in which nano-lubricants using graphene nanoplatelets (GPLs) as additives were employed. The penetrability and deposition property of GPL-oil mists under EMQL condition were investigated. The tribological and machining characteristics of GPL lubricant EMQL were compared with those of an ordinary minimum quantity lubrication (MQL) technology. The results indicated that GPL lubricant EMQL reduced coefficient of friction (COF) and worn scar diameter (WSD), as well as improved machining performance with a lower oil mist concentration compared with GPL lubricant MQL. The superior performance of GPL lubricant EMQL was attributed to the fact that the use of EMQL considerably enhanced the penetration and deposition of GPL-oil droplets to the rubbing interface, which reduced friction and wear significantly, and thus resulted in better tribological and machining performances.